PEMEROLEHAN BAHASA PADA ANAK USIA 2-3 TAHUN MELALUI METODE BERNYANYI DI PAUD NUR INSANI PIYAMAN, WONOSARI, GUNUNGKIDUL - Julananda Putri Sahasti (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2020)
Language is the main means of communication in human life in this world either in written form, oral and which is only a certain symbol. Without human language can not communicate because humans are social beings who inevitably have to interact with other humans. Language acquisition in humans begins with children when learning to speak. Language acquisition in each child is not the same, according to his age. In this research will be studied the acquisition of child language on phonology, morphology, and syntax aspects. This research uses qualitative research method with naturalistic technique. Sources of data in this study are the students of class A PAUD Nur Insani, Piyaman, Wonosari, Gunungkidul. The purpose of this study are: 1) explain the acquisition of phonology of children aged 2-3 years in early childhood Nur Insani Piyaman, Wonosari, Gunungkidul; 2) explain the acquisition of morphology of children aged 2-3 years in early childhood Nur Insani Piyaman, Wonosari, Gunungkidul; and 3) describes the acquisition of syntactics of children aged 2-3 years in early childhood Nur Insani Piyaman, Wonosari, Gunungkidul.